Курганы у села Ивано-Дарьевка (бассейн Бахмутки, северо-западный Донбасс) - Полякова, О.А.; Полидович, Ю.Б. (Археологический альманах, 2004)
In 1990-1993, near the village Ivano-Darevka (Artemovsk district of the Donetsk region), barrows No 6-7 in a group of eleven barrows and individual barrow No 1 were excavated. 23 burials of Bronze Age were investigated: These include one Pit Culture burial (No 8 in the barrow No 7), two Katakomb Culture burials (No 7, 14 in the barrow No 7), one Babino Culture burial (No 3 in the barrow No 7) and 19 Timber-Grave Culture burials. Clay vessels were found in most of them as well as in the embankments of barrows No 7 and No 1. One burial of Middle Age nomads was investigated in barrow No 6 (No 4).